Genome-wide identification and expression analysis of growth-regulating factors in Dendrobium officinale and Dendrobium chrysotoxum - Shuying Zhu; Hongman Wang; Qiqian Xue; Huasong Zou; Wei Liu; Qingyun Xue; Xiao-Yu Ding (PeerJ, 2023)
Background Dendrobium, one of the largest genera in Orchidaceae, is popular not only for its aesthetic appeal but for its significant medicinal value. Growth-regulating factors (GRFs) play an essential role in plant growth and development. However, there is still a lack of information about the evolution and biological function analysis of the GRF gene family among Dendrobiumspecies. Methods Growth-regulating factors from Dendrobium officinale Kimura et Migo and Dendrobium chrysotoxum Lindl. were identified by HMMER and BLAST. Detailed bioinformatics analysis was conducted to explore the evolution and function of GRF gene family in D. officinale and D. chrysotoxum using genomic data, transcriptome data and qRT-PCR technology. Results Here, we evaluated the evolution of the GRF gene family based on the genome sequences of D. officinale and D. chrysotoxum. Inferred from phylogenetic trees, the GRF genes were classified into two clades, and each clade contains three subclades. Sequence comparison analysis revealed relatively conserved gene structures and motifs among members of the same subfamily, indicating a conserved evolution of GRF genes within Dendrobiumspecies. However, considering the distribution of orthologous DoGRFs and DcGRFs, and the differences in the number of GRFs among species, we suggest that the GRF gene family has undergone different evolutionary processes. A total of 361 cis-elements were detected, with 33, 141, and 187 related to plant growth and development, stress, and hormones, respectively. The tissue-specific expression of GRFs showed that DoGRF8 may have a significant function in the stem elongation of D. officinale. Moreover, four genes were up-regulated under Methyl-jasmonic acid/methyl jasmonate (MeJA) treatment, showing that DoGRFs and DcGRFs play a crucial role in stress response. These findings provide valuable information for further investigations into the evolution and function of GRF genes in D. officinale and D. chrysotoxum.